The Impact Of Community Responses Toward Unlabeled Halal Peyek Crackers In The Wonomulyo Market Complex - Febrianti, Lisma; Ramayani, Indah; Asrandi , Asrandi (Jurnal Economic Resource, 2025)
This study aims to examine public responses toward "kerupuk peyek" (a traditional Indonesian cracker) sold without halal certification and to analyze its impact on purchasing decisions in the Wonomulyo Market Complex, Polewali Mandar Regency. The sale of peyek products without a halal label in traditional markets has raised doubts among some consumers, yet the product remains in demand. This research employs a descriptive qualitative approach with data collection methods including direct observation, in-depth interviews with 50 informants, and visual documentation. Informants were selected based on criteria such as productive age, traditional product consumption habits, and residence near the market. The findings indicate that public responses fall into four main categories: trustful, indifferent, doubtful, and unconcerned. Despite varied responses, all informants continued to purchase and consume the unlabeled peyek. This indicates that halal labeling is not the primary determinant of purchasing decisions, especially in traditional markets characterized by strong social and cultural values. The most influential factors include trust in sellers, long-standing consumption habits, affordable prices, and product taste. This study reveals that social values—such as close relationships between sellers and buyers and collective trust in local products—are more influential than formal considerations like halal certification. Thus, the research contributes to a deeper understanding of Muslim consumer behavior in rural areas and recommends educational and community-based approaches to increase awareness about the importance of halal labeling.